2020
DOI: 10.3390/pharmaceutics12040316
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Authorizations from EMA and FDA for Age-Appropriate Medicines Contained in the WHO Essential Medicines List for Children 2019

Jose-Manuel delMoral-Sanchez,
Isabel Gonzalez-Alvarez,
Marta Gonzalez-Alvarez
et al.

Abstract: Lack of age-appropriate commercially drug products availability is a common problem in pediatric therapeutics; this population needs improved and safer drug delivery. In addition, biopharmaceutic aspects, dosage requirements, and swallowing abilities demand pediatric forms different to adult formulations. The objective of this study was to evaluate the authorization availability from United States Food and Drug Administration (FDA) and European Medicines Agency (EMA) of oral essential medicines for children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The novel output from this study will improve the physiological understanding of the paediatric colon, aid biopredictive in silico simulations and establishing novel, more accurate in vitro assays and thus support paediatric drug development that targets the colon, resulting in more age-appropriate medicines for the paediatric population [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The novel output from this study will improve the physiological understanding of the paediatric colon, aid biopredictive in silico simulations and establishing novel, more accurate in vitro assays and thus support paediatric drug development that targets the colon, resulting in more age-appropriate medicines for the paediatric population [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous off-patent compounds can be found on the World Health Organization (WHO) Model List of Essential Medicines List for Children (EMLc), which consists of a list of the most efficacious, safe, cost-effective medicines for priority needs in children (0-12 years) [82]. In a study by delMoral-Sanchez et al, a quantitative evaluation of the age appropriateness of the commercial oral formulations listed in EMLc 7th Edition (2019) was performed [83]. The study highlighted that the percentage of oral dosage forms that resulted as authorized age-appropriate medicines by the EMA is only 52%.…”
Section: Manipulation Of Pediatric Medicinal Products: the G Gaslini ...mentioning
confidence: 99%
“…Therefore, assessing the actual marketing status may add important piece of information regarding the medicines’ availability for children. Some papers have studied the availability of, for example, paediatric oral formulations and shown variability across Europe 13–15 but, unfortunately, none of these studies have assessed the availability related to the reported outcome of the Paediatric Regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The new formulations (product group B) with an agreed-upon PIP were identified using the information from the EMA's database. 12…”
Section: Data Sourcementioning
confidence: 99%